2022-RA-999-ESGO Clinical relevance of clinicopathological and molecular factors in women with surgically treated stage IV endometrial cancer. (20th October 2022) - Nooij, Linda; Uijterwaal, Margot; Lok, Christianne; de Kroon, Cor; Kasius, Jenneke; Zweemer, Ronald; Geerestein, Cees; Horeweg, N; Bosse, Tjalling; van der Marel, Jacolien
Abstract : Introduction/Background: Risk stratification, treatment and prognosis of stage I-III endometrial cancer (EC) are dependent on its molecular subclassification. The role of this classification has not been investigated for stage IV EC. Studies on optimal treatment for stage IV EC are scarce and management is authority based and individualized. Cytoreductive surgery (CRS) combined with chemotherapy has been associated with superior overall survival (OS). This study aimes to investigate whether the molecular EC subclassification can be used as a predictive marker for successful CRS. Methodology: A retrospective cohort study was performed from 01–01–2000 until 31–12–2018 including 157 surgically-treated stage IV EC patients from five hospitals in The Netherlands. Tumour samples were molecularly classified according to the WHO 2020 classification and estrogen receptor (ER) expression status was evaluated. Molecular risk factors for intra-abdominal residual disease were identified by multivariable logistic regression analysis. OS after CRS was estimated using Kaplan-Meier's method, groups were compared using the log-rank test. Prognostic factors for OS were determined by multivariable Cox regression analyses. Results: Molecular classification shows a dissimilar distribution compared to stage I-III EC; i.e. POLE mutation ( POLE mut) 3.2%, mismatch-repair deficient (MMRd) 13.4%, no specific molecular profile (NSMP) 24.8%, p53 abnormal (p53abn) 58.6% ( table 1 ). A trend for incomplete CRS was observed for p53-abn and NSMP EC (OR 3.25, p=0.094 and OR 4.12, p=0.057 respectively), compared to MMRd EC. Complete CRS, histotype, grade and ER status had a significant impact on OS ( figure 1A-C ). Molecular classification not ( figure 1D ). Optimal (HR2.99, p<0.0001) and incomplete CRS (HR2.73, p<0.0001), grade 3 endometrioid (HR3.00, p=0.001) and non-endometrioid histotypes (HR2.50, p=0.006) were independent risk factors for shorter OS. Conclusion: Molecular classification of stage IV EC patients revealed a different distribution compared to earlier stages EC. Novel and intriguing is that molecular classification does not seem to influence surgical outcome and prognosis.